Occurrence of a mosquito vector in bird houses: Developmental consequences and potential epidemiological implications - Hamady, Dienga; Rahimah, Binti Hassan; Ahmad, Abu Hassan; Idris, Abd Ghani; Fatimah, Bt Abang; Satho, Tomomitsu; Miake, Fumio; Hamdan, Ahmad; Fukumitsu, Yuki; Nur Aida, Hashim; Wan Fatma, Zuharah; Nur Faeza, Abu Kassim; et al. (Elsevier B.V., 2015)
Even with continuous vector control, dengue is still a growing threat to public health in Southeast Asia. Main causes comprise difficulties in identifying productive breeding sites and inappropriate targeted chemical interventions. In this region, rural families keep live birds in backyards and dengue mosquitoes have been reported in containers in the cages. To focus on this particular breeding site, we examined the capacity of bird fecal matter (BFM) from the spotted dove, to support Aedes albopictus larval growth. The impact of BFM larval uptake on some adult fitness traits influencing vectorial capacity was also investigated. In serial bioassays involving a high and low larval density (HD and LD), BFM and larval standard food (LSF) affected differently larval development. At HD, development was longer in the BFM environment. There were no appreciable mortality differences between the two treatments, which resulted in similar pupation and adult emergence successes. BFM treatment produced a better gender balance. There were comparable levels of blood uptake and egg production in BFM and LSF females at LD; that was not the case for the HD one, which resulted in bigger adults. BFM and LSF females displayed equivalent lifespans; in males, this parameter was shorter in those derived from the BFM/LD treatment. Taken together these results suggest that bird defecations successfully support the development of Ae. albopictus. Due to their cryptic aspects, containers used to supply water to encaged birds may not have been targeted by chemical interventions.